2014
DOI: 10.1177/0363546514530292
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment of Large Knee Osteochondral Lesions With a Biomimetic Scaffold

Abstract: The study findings indicate that the biomimetic scaffold that was investigated is an off-the-shelf, cell-free, and cost-effective implant that can regenerate either cartilage or subchondral bone. The scaffold allows a 1-step surgical procedure that can be used for osteochondral lesions, OCD, and in some cases osteonecrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…Development of cell-free scaffolds (chondrocytes) has arisen with the purpose of inducing tissue regeneration through the proliferation and migration of mesenchyme cells 15) . Also, scaffolds would be able to sustain the clot created after microfractures or nanofractures and increase the success rate in medial condyle lesions 16) .…”
Section: Discussionmentioning
confidence: 99%
“…Development of cell-free scaffolds (chondrocytes) has arisen with the purpose of inducing tissue regeneration through the proliferation and migration of mesenchyme cells 15) . Also, scaffolds would be able to sustain the clot created after microfractures or nanofractures and increase the success rate in medial condyle lesions 16) .…”
Section: Discussionmentioning
confidence: 99%
“…It has shown promising clinical results in osteochondral defects of up to 3 to 8 cm 2 on the femoral condyles, trochlea, and tibial plateau; however, the biological repair potential of the scaffold has recently been questioned. 35 Authors have reported preoperative to 1 year IKDC increases from 36 ± 6 to 68 ± 13, 36 45 ± 19 to 71 ± 18, 37 and 48 ± 18 to 76 ± 13 38 (mean IKDC increase 32, 26, and 28 respectively). In the present study, the ADTT treatment resulted in an IKDC increase from preoperative to 1 year of 36 ± 20 to 68 ± 15—a statistically and clinically significant increase of 32 points, which is similar to or better than previously published studies investigating methods for osteochondral repair.…”
Section: Discussionmentioning
confidence: 99%
“…Berruto et al 29 described the use of MaioRegen (Fin-Ceramica Faenza SpA, Faenza, Italy) in the treatment of large knee osteochondral lesions. They enrolled 49 patients in the study (mean defect size, 4.35 cm 2 ).…”
Section: Resultsmentioning
confidence: 99%
“… 28 Conversely, the treatment of osteochondral lesions with MaioRegen showed promising results in terms of survivorship at short term. 29 …”
Section: Discussionmentioning
confidence: 99%